The Relevance of Commendable Attitudes and Actions Standards to the Commutation of the Death Penalty in Indonesia's Criminal Code - Adhim, Muhammad Iqbal Maulana; Erny Herlin Setyorin (International Journal of Social Sciences and Humanities, 2025)
One of the important updates in the National Criminal Code is the implementation of the conditional death penalty, which provides an opportunity for death row inmates to change their sentence to life imprisonment if they show commendable attitudes and actions during the probation period. The study found that the phrase "commendable attitudes and deeds" refers to sincere remorse, adherence to rules, and positive contributions during the probationary period. However, this article does not yet have clear guidelines or indicators, thus posing challenges in its implementation, including potential subjectivity and inconsistencies in assessments. This study aims to find out how starndart determines commendable attitudes and actions in Article 100 Paragraph (4) of Law Number 1 of 2023 concerning the Criminal Code. The method used in this study is normative juridical using a statutory approach and a conceptual approach. The results of this study are that the phrase "commendable attitudes and deeds" refers to sincere remorse, adherence to the rules, and positive contributions during the trial period. However, this article does not have clear guidelines or indicators, thus posing challenges in implementation, including the potential for subjectivity and inconsistency in assessment. The process of converting the death penalty to life imprisonment involves reports from correctional institutions, third-party testimony, and Presidential Decrees based on the Supreme Court's considerations. This research suggests the development of objective and systematic evaluation standards to ensure legal fairness and consistency.